Differential release of manure-borne bioactive phosphorus forms to runoff and leachate under simulated rain. - Blaustein, R.A.; Dao, Thanh H.; Pachepsky, Y.A.; Shelton, D.R. (Journal of Environmental Management, 2017)
Limited information exists on the unhindered release of bioactive phosphorus (P) from a manure layer to model the partitioning and transport of component P forms before they reach an underlying soil. Rain simulations were conducted to quantify effects of intensity (30, 60, and 90 mm h −1 ) on P release from an application of 60 Mg ha −1 of dairy manure. Runoff contained water-extractable- (WEP), exchangeable and enzyme-labile bioactive P (TBIOP), in contrast to the operationally defined “dissolved-reactive P” form. The released P concentrations and flow-weighed mass loads were described by the log-normal probability density function. At a reference condition of 30 mm h −1 and maintaining the surface at a 5% incline, runoff was minimal, and WEP accounted for 20.9% of leached total P (TP) concentrations, with an additional 25–30% as exchangeable and enzyme-labile bioactive P over the 1-h simulation. On a 20% incline, increased intensity accelerated occurrence of concentration max and shifted the skewed P concentration distribution more to the left. Differences in trends of WEP, TBIOP, or net enzyme-labile P (PHP o ) cumulative mass released per unit mass of manure between intensities were attributable to the higher frequency of raindrops striking the manure layer, thus increasing detachment and load of colloidal PHP o of the water phases. Thus, detailed knowledge of manure physical characteristics, bioactive P distribution in relation to rain intensity, and attainment of steady-state of water fluxes were critical factors in improved prediction of partitioning and movement of manure-borne P under rainfall.